The cauliflower mosaic virus reverse transcriptase is not produced by the mechanism of ribosomal frameshifting in Saccharomyces cerevisiae - Wurch, T. (Virology, 1991)
The capsid protein and the reverse transcriptase of cauliflower mosaic virus (CaMV) are encoded by two genes (ORF IV and ORF V) that lie in different translation reading frames. A comparison can be drawn between the synthesis of both CaMV proteins and the fusion protein in a yeast retrotransposon, Ty, resulting from a +1 frameshifting event which fuses two out-of-phase ORFs encoding the structural protein and the reverse transcriptase of Ty. For this reason, we constructed a yeast expression vector containing CaMV ORF VII fused to CaMV ORF III by a fragment of 452 bp including the overlapping region of ORF IV and ORF V, ORF VII and ORF III being used as reporter genes. We characterized two proteins (22 and 50 kDa) synthesized from this plasmid in the yeast expression system. We demonstrated that the 50-kDa polypeptide is not synthesized from a +1 frameshifting event but is probably a dimeric form of the 22-kDa protein. From this result we conclude that the CaMV reverse transcriptase is not produced by a mechanism of ribosomal frameshifting.